Impact of Pricing for Sustaining Banana Retailing Business in Tanzania: A Case Study of the Mbuyuni Market - Leyla Mziray; Amembah A. Lamu Amos; Ladis Komba (Journal of Management and Entrepreneurship Research, 2026)
Objective: This study aimed to examine the impact of pricing strategies on creating sustainable value among banana retailing businesses at Mbuyuni Market in Tanzania. Research Design & Methods: A mixed-method approach was employed, integrating quantitative and qualitative data analysis techniques. Data were collected from 259 banana retailers and customers, and reliability was tested using Cronbach’s Alpha to ensure internal consistency of the measurement scales. Findings: The results revealed that inadequate pricing knowledge, weak market strategy understanding, lack of social recognition and respect, and insufficient rewards significantly affect business sustainability. Appropriate and fair pricing strategies were found to enhance customer loyalty, sales growth, and profitability. Flexible pricing aligned with market demand and quality service delivery also positively influenced long-term business sustainability. Implications & Recommendations: The study recommends that banana retailers adopt flexible and market-responsive pricing strategies, strengthen customer-oriented service practices, address customer feedback effectively, and improve strategic market planning. Regular training on pricing and market management is also encouraged to enhance competitiveness and sustainability. Contribution & Value Added: Theoretically, the study enriches the understanding of pricing as a strategic tool for sustaining small retail businesses in developing market contexts. Practically, it provides actionable insights for retailers and policymakers to strengthen pricing capabilities and promote sustainable growth in informal retail markets in Tanzania.